2017
DOI: 10.1111/aogs.13080
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization healthcare professionals generally underestimate patients’ satisfaction with quality of care

Abstract: The results of this study will increase the professionals' understanding of the patients' experiences during IVF treatment and provide additional knowledge when identifying areas to prioritize to improve quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…5 It should be kept in mind that HCPs tend to underestimate actual given care and overestimate the importance of different aspects of care compared with patients' perceptions. 32,33 In the present study, HCPs scored low values regarding perceptions of given care (PR) for a great number of items related to symptom relief, spiritual and existential needs, information, patient participation, continuity of care, care planning, cooperation, and coordination of care services, all of which are important components of high-quality person-centred palliative care. 4 None of the care areas received balanced high PR and SI scores, which is interpreted as indicating that the ability of services to meet patients' preferences was low.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…5 It should be kept in mind that HCPs tend to underestimate actual given care and overestimate the importance of different aspects of care compared with patients' perceptions. 32,33 In the present study, HCPs scored low values regarding perceptions of given care (PR) for a great number of items related to symptom relief, spiritual and existential needs, information, patient participation, continuity of care, care planning, cooperation, and coordination of care services, all of which are important components of high-quality person-centred palliative care. 4 None of the care areas received balanced high PR and SI scores, which is interpreted as indicating that the ability of services to meet patients' preferences was low.…”
Section: Discussionmentioning
confidence: 78%
“…Other studies using the QPP instrument to assess care quality show that HCPs tend to underestimate actual care received and overestimate how important different aspects of care are, compared with patients' perceptions. 32,33 Nevertheless, examining HCPs' perceptions of care provided, and how important they perceive the care to be for patients, allows important knowledge for improvement and development of palliative care to be obtained without burdening fragile patients and their families. This study aimed to investigate perceptions of HCPs working in a combined acute oncology-palliative care unit regarding quality of palliative care received by the patients and how important the care was to the patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a discrete choice experiment in Dutch and Belgian fertility clinics, reproductive specialists overestimated how much patients value pregnancy rates and underestimated the value patients place on patient-centered care [ 4 ]. Research from Sweden has evaluated the quality of fertility care as perceived by men, women, and health care professionals [ 5 7 ]. Overall, relatively little empirical work on patient-centered care has been conducted, especially in the United States (US), where health insurance coverage of testing and treatment varies widely by state.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically with regard to FT, providers appeared to underestimate the importance of PCC for patient satisfaction [20,24,25], thereby suggesting that PCC in FT may be in need of improvement [26]. Specifically, the dimensions of PCC that are most important to patients might be different from those considered most important to providers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…information and communication vs coordination and integration of care, respectively) [27]. Interestingly, while the data in some studies indicated that healthcare professionals underestimated their own performance [6] the data in others emphasize the opposite [25]. The aforementioned studies generally instructed the healthcare professional to answer the way their patients would have evaluated the patient-centered quality of care at their clinic.…”
Section: Introductionmentioning
confidence: 99%